Spatial variability of PAH load of urban wet weather pollution in the Parisian combined sewer - Gasperi, P.J.; Moilleron, R.; Chebbo, G. (Houille Blanche-Revue Internationale De L Eau, 2005)
The OPUR (Observatory of Urban pollutants) research programme created in Paris an experimental on-site observatory urban pollutant loads in combined sewer systems in order to characterise the dry and wet weather flows, Lit different spatial scales. This article presents the first results on the spatial variability of the PAH load during wet weather flow (WWF). At the scale of a rain event, investigations revealed that (i) PAH concentrations were relatively homogenous whatever the spatial scale and were greater than those of the dry weather flow (DWF); (ii) PAH distributions between dissolved and particulate phases were constant and (iii) PAH fingerprints exhibited a similar pattern for all the catchments. Moreover; an evaluation of the contribution of DWF runoff and erosion of sewer deposits to WWF load was established. At the scale of the Marais catchment, the contributions were evaluated at 14, 8 and 78 %, respectively. For all the catchments, runoff contribution was found quite constant and evaluated at about 10 %, according to calculation hypothesis. The DWF contribution was greater for bigger catchments (> 900 ha) when compared to the Marais catchment (42 ha). On the contrary, the sewer erosion contribution was lower for larger catchment, but still remains an important source of pollution.